Immune responses in mice to different noncovalent complexes of meningococcal B polysaccharide and outer membrane proteins. - Lifely, M R (1988)
Noncovalent complexes of meningococcal group B polysaccharide and outer membrane proteins (OMPs) from serotypes 2a, 2b, 6, 8, and 15 were made either by coextraction of the two components from culture supernatants or by separate preparation of both OMPs and B polysaccharide with subsequent mixing of the two components. The former method showed a markedly greater degree of binding of B polysaccharide to OMPs, a less heterogeneous composition of OMPs, and a lower lipopolysaccharide content. Immunization of mice with these complexes showed that a higher degree of binding of B polysaccharide to OMPs resulted in a higher anti-B response. Western blotting (immunoblotting) and solid-phase radioimmunoassay techniques confirmed that antibody cross-reactions occur among OMP serotypes. The occurrence of common T-cell determinants between OMP serotypes was suggested when mice primed with a type 6 OMP complex and challenged with a homologous or heterologous serotype complex responded with significantly higher anti-B titers than unprimed animals. These memory T cells persisted for at least 12 months in mice.